Multikulturalisme dalam Novel Pelangi Melbourne: Dua Dunia Satu Cinta Karya Zuhairi Misrawi - Novita, Rina; WS, Hasanuddin; Nurizzati, Nurizzati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
This article to desrcibe multiculturalism in the novel Pelangi Melbourne: Dua Dunia Satu Cinta author by Zuhairi Misrawi.To get the purpose use the study of kualitative with descriptive analyst method. The data collected use the writing format and identivication of data. The data to analyst and interpretation. The find of study to display that in the novel Pelangi Melbourne: Dua Dunia Satu Cinta author by Zuhairi Misrawi finded the element of multiculturalism as is. There is (1) solidarity and brotherhood, (2) open trading, (3) family values​​, (4) respect for ethics, (6) was enough in life, (7) and sharing and control of power.